2019
DOI: 10.1101/799759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An endogenous glucocorticoid-cytokine signaling circuit promotes CD8+T cell dysfunction in the tumor microenvironment

Abstract: Identifying signals in the tumor microenvironment (TME) that promote CD8 + T cell dysfunction can inform improved therapeutic approaches for cancer. Here, we identify that Nr3c1, the gene encoding the glucocorticoid receptor (GR), is highly expressed in dysfunctional CD8 + tumor-infiltrating lymphocytes (TILs). The GR transactivates expression of multiple checkpoint receptors and loss of GR in CD8 + T cells limits dysfunctional phenotype in CD8 + TILs resulting in improved tumor growth control. We show that gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Therefore, corticosteroid treatment during immune checkpoint blockade may impact the response to low affinity tumor antigens by suppressing fatty acid metabolism of these cells. Notably, it was recently shown that glucocorticoids are synthesized locally in tumor microenvironments by various cell types including myeloid lineages, macrophages and T cells themselves, meaning that their effects on T cell metabolism and function may be particularly relevant in the context of solid tumors ( 158 , 159 ) ( Table 1 ).…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…Therefore, corticosteroid treatment during immune checkpoint blockade may impact the response to low affinity tumor antigens by suppressing fatty acid metabolism of these cells. Notably, it was recently shown that glucocorticoids are synthesized locally in tumor microenvironments by various cell types including myeloid lineages, macrophages and T cells themselves, meaning that their effects on T cell metabolism and function may be particularly relevant in the context of solid tumors ( 158 , 159 ) ( Table 1 ).…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…As such, future work is necessary to disentangle the molecular circuitry of androgen, Tcf1 and type I IFN. In this regard, there exists significant precedent for the involvement of Nuclear Receptor family members, including NR4A 4649 and NR3C1 (glucocorticoid receptor) 50 , in CD8 + T cell exhaustion. Finally, our work showing sex specific CD8 + TIL behavior in bladder cancer highlights the broader opportunities for discovery due to sex disparities in health and disease.…”
Section: Discussionmentioning
confidence: 99%